Plasmin digest of κ-casein as a source of antibacterial peptides. Issue 2 (May 2014) - Sedaghati, Marjaneh; Ezzatpanah, Hamid; Boojar, Masoud Mashhadi Akbar; Ebrahimi, Maryam Tajabadi; Aminafshar, Mehdi
<x content-type="archive" xml:space="preserve">Abstract</x> This study investigated the antibacterial properties of plasmin, the plasmin hydrolysis of bovine κ-casein and the fractions (named κC1, κC2, κC3, κC4, and κC5) liberated from it using RP-HPLC. The target bacteria were Escherichia coli, Staphylococcus aureus (pathogenic), Lactobacillus casei and Lactobacillus acidophilus (probiotic). Three peptides (kC1, kC3, and kC4) were found to have antibacterial activity, with κC3 peptide being the most active. The plasmin digest of bovine κ-casein proved to be stronger than any of its fractions in terms of antibacterial potential. Measurement of the minimum inhibitory concentration (MIC) showed that Gram-positive bacteria are generally more sensitive to antibacterial activity than Gram-negative bacteria. The MIC of nisin, as a bacteriocin peptide, was also measured. The three antibacterial peptides were identified using LC-Mass. The molecular mass of kC1, kC3, and kC4 corresponded to the f(17–21), f(22–24), and f(1–3) of bovine κ-casein, respectively. It was also found that the positive charge and hydrophobicity of a peptide are not key factors in antibacterial activity. On the whole, the present study demonstrated that the plasmin digest of κ-casein has a high antibacterial potential and can be considered as a natural antibacterial agent in the food chain.